Association of cholecystectomy with osteoporosis risk: a prospective study using data from the UK Biobank - Yang, Qin; Wang, Ming; Zhang, Tongtong; Wen, Jun; Long, Lu; Xia, Congying (Frontiers in Endocrinology, 2023)
Objective To investigate whether prior cholecystectomy is associated with incident osteoporosis. Background Cholecystectomy may have consequences involving abnormal metabolism. Studies investigating the association between prior cholecystectomy and osteoporosis have yielded inconsistent results. Methods In total, 17,603 UK Biobank participants underwent cholecystectomy, and 35,206 matched controls were included in this study. They were followed up for incident osteoporosis, which was determined using ICD-10 codes (M80–82). The association between cholecystectomy and osteoporosis was assessed using Cox proportional regression modeling. The association between osteoporosis risk and cholecystectomy was further analyzed across age, sex, serum vitamin D level, and body mass index (BMI) categories. Results Within a median follow-up period of 13.56 years, 3,217 participants were diagnosed with osteoporosis. After adjustment for relevant confounders, prior cholecystectomy was associated with a 1.21 times higher risk of osteoporosis in women (hazard ratio (HR): 1.21 [95% CI, 1.12–1.31], p < 0.001) and a 1.45 times higher risk in men (HR: 1.45 [95% CI, 1.10–1.90], p = 0.007). In women, the association was stronger for patients who were aged 40–55 years, with BMI < 18.5 kg/m2, and vitamin D between 30 and 50 nmol/ml. No significant interactions between cholecystectomy and income level, education level, presence of hypertension, or diabetes were identified in either sex. Conclusions Our findings indicated that people who underwent cholecystectomy had a higher risk of developing osteoporosis after adjustment for potential confounders. Our findings suggest that awareness of the risk of osteoporosis in patients with a history of cholecystectomy is merited.